Application of Integrated-Weight Water Quality Index in Groundwater Quality Evaluation - Thanh Giao Nguyen; Kim Anh Phan; Thi Hong Nhien Huynh (Civil Engineering Journal, 2022)
Groundwater is one of the most crucial freshwater resources in many parts of the world. However, the growth of the population and different economic activities have negatively impacted groundwater quality. This study aims to assess the groundwater quality in An-Giang province, Vietnam, from 2017–2020 and investigate its suitability for drinking via a new integrated-weight water quality index (IWQI). The samples were collected at thirteen wells in dry and rainy seasons and analyzed for eleven physicochemical parameters, including pH, total dissolved solids (TDS), total hardness, nitrate (NO3ˉ), ammonium (NH4+), iron (Fe), manganese (Mn), arsenic (As), mercury (Hg), lead (Pb), and coliform. These values were compared to the Vietnamese standard. The entropy weight method and the Criteria Importance Though Inter-criteria The correlation weighting method was integrated to compute the weights in IWQI. The results showed that NH4+and coliform concentrations were consecutively higher than the standard over the study period. No detection of As, Hg, and Pb concentrations in groundwater was in 2019 – 2020. There were significant statistical differences between parameters from 2017–2020 in the dry and rainy seasons. The results of IWQI revealed that about 40% of the total samples in 2020 were categorized as unsuitable for drinking. IWQI values range from 72 to 7973 in 2020, 12 to 3020 in 2019, 21 to 1115 in 2018, and 53 to 2246 in 2017. Most samples with high IWQI values are located near the burial pits of African fever-infected swine. The findings of this study could provide further information about the changes in groundwater quality from 2017–2020 in An Giang province, Vietnam, and the IWQI method can be proposed for other studies to evaluate groundwater quality effectively. Doi: 10.28991/CEJ-2022-08-11-020 Full Text: PDF